Fictions coloniales : autoréférentialité et activisme indigène dans les collages de Denilson Baniwa - Claudia Mattos Avolese (Brésil(s))
This article examines the series « Colonial Fictions » by the Brazilian Indigenous artist Denilson Baniwa, in which he introduces characters from popular sci-fi movies into ethnographic photographs shot in the Brazilian Amazon by the German Ethnographer Theodor Koch-Grünberg. The paper contextualizes the series within Denilson’s wider artistic project of destabilizing traditional historical narratives to promote the emergence of suppressed indigenous perspectives.